TINDAK TUTUR PERLOKUSI DALAM ROMAN BUMI MANUSIA KARYA PRAMOEDYA ANANTA TOER - Ari Rizky Akbar; Sisiliya Saman; Ahmad Rabi’ul Muzammil (Universitas Tanjungpura, 2019)
AbstractThis study aims to describe the types and functions of perlocution speech acts in the Romance Bumi Manusia Karya Pramoedya Ananta Toer, and to describe the form of review text and the Lesson Plan model about Romance Bumi Manusia Karya Pramoedya Ananta Toer as the implication of the results of the study into the Indonesian Language lesson, 2013 Curriculum. This qualitative research was conducted using the descriptive method with an inductive approach. The data source in this study was the Romance Bumi Manusia Karya Pramoedya Ananta Toer. The data collected were the whole conversation related to perlocution speech acts. The technique of data collection used was a documentary study. The data collection tool and instrument used were the researcher himself since the study is document analysis. The data were analyzed by using the speaking analysis technique. Based on the data analysis, the perlocution speech acts founds in the romance are assertive, directive, expressive, and declarative. From the findings, the dominant speech acts found are directive. The function applied in this study is competitive, fun, teamwork, and conflict. This research provides a review text and the 2013 Curriculum lesson plan model for class VIII in semester 2. Keywords: perlocution speech acts, Romance bumi manusia